The Impact of Microparticulate Air Pollution in Polycystic Ovary Syndrome: A Narrative Review - Narelle Stegehuis; Vicki Kotsirilos; Jim Parker (IMR Press, 2024)
Objective: The aim of this narrative review is to summarize studies examining the relationship between microparticulate air pollution (MAP) and polycystic ovary syndrome (PCOS). Mechanism: PCOS is increasingly regarded as an evolutionary mismatch disorder that manifests in women due to exposure to a range of lifestyle and environmental factors. Although the underlying causes of PCOS remain debated, environmental factors such as endocrine-disrupting chemicals (EDC), may contribute to its pathogenesis due to their well-documented hormonal and metabolic effects. MAP is another significant environmental exposure that has been associated with a variety of chronic diseases, as well as adverse hormonal and metabolic effects, including PCOS. Chronic low-grade inflammation and insulin resistance (IR) are key pathophysiological features of PCOS that have been associated with inhalation and ingestion of MAP. Findings in Brief: Our search identified four studies that systematically examined the relationship between MAP and PCOS. One population-based cohort study showed an increased risk of PCOS with increased exposure to various air pollutants, including MAP. A second population-based study showed a decreased risk of PCOS with increasing levels of exposure, while a longer duration of exposure was associated with an increased risk of PCOS. A third study found that conception rates were lower in women with PCOS exposed to second-hand smoke (SHS) compared to non-exposed women. In contrast, a fourth study reported that exposure to air pollutants was not associated with reduced pregnancy outcomes. These data suggest that both the concentration and duration of exposure to MAP may be important factors, and that reproductive outcomes could be affected by exposure to MAP through second-hand cigarette smoke. Conclusions: Preliminary data suggest that MAP may contribute to an increased risk of PCOS, although the available evidence remains inconsistent. Nevertheless, the current evidence supports advising women to avoid exposure to SHS and MAP whenever possible. This review highlights the need for further research on the effects of MAP in women with PCOS.